The TAM family receptor tyrosine kinase TYRO3 is a negative regulator of type 2 immunity - Chan, Pamela Y. (2016)
Host responses against metazoan parasites or an array of environmental substances elicit type 2 immunity. Despite its protective function, type 2 immunity also drives allergic diseases. The mechanisms that regulate the magnitude of the type 2 response remain largely unknown. Here, we show that genetic ablation of a receptor tyrosine kinase encoded byTyro3in mice or the functional neutralization of its ortholog in human dendritic cells resulted in enhanced type 2 immunity. Furthermore, the TYRO3 agonist PROS1 was induced in T cells by the quintessential type 2 cytokine, interleukin-4. T cell-specificPros1knockouts phenocopied the loss ofTyro3 Thus, a PROS1-mediated feedback from adaptive immunity engages a rheostat, TYRO3, on innate immune cells to limit the intensity of type 2 responses.